TAXES TO REGIONAL FISCAL CAPACITY: THE CASE OF ENTERTAINMENT AND STREET LIGHTING TAXES - Retno Murnisari; Martina Sari (JAT : Journal Of Accounting and Tax, 2025)
The purpose of this research is to determine the extent of the contribution of Pajak Hiburan and Pajak Penerangan Jalan  to the Pendapatan Asli Daerah (PAD) in the city of Blitar from 2019 to 2024. The method used in this study is quantitative. The data used is secondary data, which is the report of targets and realization of Pendapatan Asli Daerah for the years 2019-2024. Data analysis uses the contribution formula by comparing the realization of the Pajak Hiburan or Pajak Penerangan Jalan to the realization of PAD per year from 2019 to 2024, then multiplying by 100%. The results of the data management show that the contribution of the Pajak Hiburam to the Pendapatan Asli Daerah (PAD) in the city of Blitar from 2019 to 2024 is on average 0.68%, which falls into the very low category. This is due to the small number of taxpayers. Meanwhile, the contribution of the Pajak Penerangan Jalan  to the Pendapatan Asli Daerah  in Blitar city from 2019 to 2024 is an average of 6.43%, which falls into the very low category. This occurs because the potential of the PPJ is only sourced from PLN, and there are many other components that affect the PAD.